2021
DOI: 10.3390/su13168988
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Food and Plastic Waste Generated by Consumers in Bangkok

Abstract: The crisis ignited by COVID-19 has transformed the volume and composition of waste generation and requires a dynamic response from policy makers. This study selected Bangkok as a case study to semi-quantitatively examine the impact of the COVID-19 outbreak on consumer-generated food and plastic waste by examining changes in lifestyles and consumption behaviour through a face-to-face questionnaire survey. Travel bans and diminished economic activity due to COVID-19 have led to a dramatic reduction in waste from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 33 publications
3
45
0
Order By: Relevance
“…Studies on the impact of COVID-19 on household food waste have also reported contradictory results. Although Amicarelli and Bux (2021) and Burlea-Schiopoiu et al (2021) reported reductions in household food waste during COVID-19 in Italy and Romania, Berjan et al (2021) and Liu et al (2021) reported higher amounts of food waste in Serbia and Thailand. The impacts of COVID-19 on the amount of food wasted depends on various socio-demographic (e.g., household size and the number of children), socio-economic (e.g., income loss, governmental restrictions), behavioural (e.g., developing cooking skills, better meal planning, more efficient stocking), psychological (e.g., depression, fear, stress), situational (e.g., individuals’ available time), and cultural (e.g., eating at a restaurant) factors ( Everitt et al, 2021 ; Özbük et al, 2021 ; Qian et al, 2020 ).…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Studies on the impact of COVID-19 on household food waste have also reported contradictory results. Although Amicarelli and Bux (2021) and Burlea-Schiopoiu et al (2021) reported reductions in household food waste during COVID-19 in Italy and Romania, Berjan et al (2021) and Liu et al (2021) reported higher amounts of food waste in Serbia and Thailand. The impacts of COVID-19 on the amount of food wasted depends on various socio-demographic (e.g., household size and the number of children), socio-economic (e.g., income loss, governmental restrictions), behavioural (e.g., developing cooking skills, better meal planning, more efficient stocking), psychological (e.g., depression, fear, stress), situational (e.g., individuals’ available time), and cultural (e.g., eating at a restaurant) factors ( Everitt et al, 2021 ; Özbük et al, 2021 ; Qian et al, 2020 ).…”
Section: Introductionmentioning
confidence: 94%
“…Studies conducted in Italy, Russia, the US, Bosnia, Romania, Spain, Canada, Germany, Turkey, Lebanon, Mexico, Japan, Qatar, Tunisia, and Portugal all reported less food waste (e.g., Babbitt et al, 2021 ; Profeta et al, 2021 ; Vittuari et al, 2021 ). However, studies conducted in Thailand ( Liu et al, 2021 ), Serbia ( Berjan et al, 2021 ), and the UK ( Filimonau et al, 2021 ), and one international study in 23 countries ( Filho et al, 2021 ) found an increase in food waste. Most of these studies relied on self-reported food waste ( Table 3 ), which is subject to bias, so their results should be interpreted with caution.…”
Section: Thematic Analysismentioning
confidence: 99%
See 3 more Smart Citations